Recapturing the History and Rights of First Nations Peoples of British Columbia: A Political Analysis of Past and Present Relationships with the Dominion of Canada - Pascoe, Anita (2002)
The recognition of aboriginal title and rights has continued to evolve in federal and provincial policies. The constant flux of recognition and renunciation has created a unique First Nations and European history.1 This paper will address the start of colonial policy and will dissect the changes that decreased the supremacy of First Nations peoples. It should be noted the word Indigenous will be used interchangeably with the term First Nations. Indigenous is defined as “originating in and characteristic of a particular region or country.”2 This distinction is made in acknowledgment of particular nations who view the term Nations as a European imposed term Graduate